Adoption and up gradation of CMMI : prospect of software industry of Bangladesh - Haque, Samirul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.